(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: Determination of occupational stress status and some related factors of health workers from clinical departments at MEDLATEC Hospital in 2020. Subjects and research methods: Cross-sectional descriptive design, combining qualitative and quantitative. Occupational stress is determined by the DASS 21 Scale for 250 health workers. Results and discussions: The stress rate of the health workers in the study is 41.6%. In which, 30.8% of subjects had mild stress, 62.5% of subjects suffered from moderate stress and 6.7% of subjects suffered severe stress. No subjects experienced very severe stress. The results of multivariate logistic regression analysis showed that health workers have the following characteristics: they are currently taking care of their elderly, frail and sick relatives; encountering traffic jams, traffic accidents from home to work; often have to work with high intensity of work; Feeling that a job that is not respected has a stress risk of 2,466; 4,3; 3,516 and 6,781 times higher than that of health workers who are not in the same situation (p <0.05). Employees who do not regularly receive support from their superiors are 3,811 times more likely to stress than those who receive this support regularly (p <0.001). Conclusions and recommendations: The MEDLATEC Hospital need screening to detect doctors, nurses showing signs of stress to take support measures to reduce stress for them; building salary, welfare, civilized and professional working environment, better infrastructure and infrastructure. Health workers also Objectives: Determination of occupational stress status and some related factors of health workers from clinical departments at MEDLATEC Hospital in 2020. Subjects and research methods: Cross-sectional descriptive design, combining qualitative and quantitative. Occupational stress is determined by the DASS 21 Scale for 250 health workers. Results and discussions: The stress rate of the health workers in the study is 41.6%. In which, 30.8% of subjects had mild stress, 62.5% of subjects suffered from moderate stress and 6.7% of subjects suffered severe stress. No subjects experienced very severe stress. The results of multivariate logistic regression analysis showed that health workers have the following characteristics: they are currently taking care of their elderly, frail and sick relatives; encountering traffic jams, traffic accidents from home to work; often have to work with high intensity of work; Feeling that a job that is not respected has a stress risk of 2,466; 4,3; 3,516 and 6,781 times higher than that of health workers who are not in the same situation (p <0.05). Employees who do not regularly receive support from their superiors are 3,811 times more likely to stress than those who receive this support regularly (p <0.001). Conclusions and recommendations: The MEDLATEC Hospital need screening to detect doctors, nurses showing signs of stress to take support measures to reduce stress for them; building salary, welfare, civilized and professional working environment, better infrastructure and infrastructure. Health workers also